Lumières of the English Criticism (Introductory Article). Samuel Johnson. Swift (From The Lives of the Most Eminent English Poets). Translated into Russian, with Notes - Natalya I. Reinhold (Studia Litterarum)
This publication includes the introductory article and the translation of the source text, namely, “The Life of Swift” from The Lives of the Most Eminent English Poets (1781) by Samuel Johnson (1709–1784), a great eighteenth-century English literary critic and biographer. The author points at the paradox-like case of Samuel Johnson’s reception in Russia, with his magnum opus hasing been left untranslated into Russian. The article draws numerous examples of the unacknowledged borrowings from Johnson’s Lives made by the nineteenth-and twentieth-century Russian critics and scholars. The article highlights various aspects of Johnson’s versatile activities as a biographer and critic, an essay master and a compiler of the dictionary, a playwright and a poet, an editor and a publisher of commentaries and notes, a writer of pamphlet and letter writing, and last but not least, a good Christian who had left a collection of prayers and meditations. The article provides a detailed description of the source text in question, and defines its status among Johnson’s works and in English letters at large. The author of the article claims Johnson to be the true founder of the literary-cum-biographical-cum-critical essay eighteenth-century in England. She mentions the forthcoming publication of the first full-text translation of The Lives of the Most Eminent English Poets into Russian in the book series “Literaturnye pamyatniki,” and gives as a sample the translation of “The Life of Swift,” accompanied by notes.